Tourism Marketing Strategies from Price Tags to Brand Value - Yang, Shan-Kuei; Tsai, Chin-Fa; Leelapattana, Winitra; Thongma , Weerapon (Journal of Ecohumanism, 2025)
The tourism industry’s dynamic and competitive landscape necessitates innovative marketing strategies that align pricing models with brand identity to attract and retain travelers. This review critically examines the interplay between pricing strategies, branding, and consumer behavior in tourism marketing, highlighting how these interconnected elements shape destination appeal and market competitiveness. It explores diverse pricing approaches—dynamic, cost-based, and value-driven—and their influence on brand equity, consumer perceptions, and purchasing behavior. The integration of traditional and digital marketing methods is analyzed, focusing on the transformative role of experiential marketing, storytelling, and digital platforms in fostering brand loyalty and enhancing market positioning. Key challenges, such as balancing affordability with premium brand perceptions, addressing over-tourism, and adapting to sustainability imperatives, are explored through real-world case studies from successful tourism campaigns. Emerging trends, including AI-driven personalization, eco-conscious branding, and the rising demand for immersive and transformative travel experiences, are also examined to offer actionable insights for the future of tourism marketing. The findings underscore the importance of cohesive marketing strategies integrating pricing, branding, and consumer behavior to drive consumer loyalty, revenue growth, and sustainable impact. This review provides practical recommendations for tourism businesses and policymakers. It identifies future research directions to navigate the evolving pricing, branding, and consumer preferences dynamics in a rapidly changing global tourism landscape.